1962
DOI: 10.1136/bmj.1.5277.510
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coronary Atherosclerosis in Northern India

Abstract: We thank Mr. M. P. Curwen for statistical advice and Miss W. Smith for her help in the follow-up study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1963
1963
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…11 Virmani et al also observed that maximum cases were seen between fourth and fifth decades of life and advanced atherosclerotic lesions were predominant in this age group. 12 In our study also, advanced atherosclerotic lesions were more commonly seen in older age groups, viz fifth to seventh decades of life ( [13][14][15][16][17][18] Marwah et al also found significant atherosclerosis in hearts of all cases more than 70 years of age, in their autopsy study on sudden cardiac deaths. 19 In our study, male to female ratio was 4.3:1 with 76.5% males and 23.5% of cases being females.…”
Section: Discussionsupporting
confidence: 57%
“…11 Virmani et al also observed that maximum cases were seen between fourth and fifth decades of life and advanced atherosclerotic lesions were predominant in this age group. 12 In our study also, advanced atherosclerotic lesions were more commonly seen in older age groups, viz fifth to seventh decades of life ( [13][14][15][16][17][18] Marwah et al also found significant atherosclerosis in hearts of all cases more than 70 years of age, in their autopsy study on sudden cardiac deaths. 19 In our study, male to female ratio was 4.3:1 with 76.5% males and 23.5% of cases being females.…”
Section: Discussionsupporting
confidence: 57%
“…Overall incidence of significant atherosclerotic lesions was 25.11% in right and 29.76% in left coronary artery. Earlier studies also in India by Wiget al [32] found significant atheroma in two-third of cases above the age of 20 years while Tandon [22] found atherosclerosis in second and thirddecade. Singh et al [20] found atherosclerosis atthe age of 17 years.…”
Section: Discussionmentioning
confidence: 94%
“…Populations in which important data have been collected are among white, Bantu and other racial groups [150-1611 in Africa, the various ethnic subdivisions in Israel [162-1691, groups in India [170-1781, Japan [179-1831, China [184, 1851, the Pacific area [186-1921and in South and Central America [193-1971 It seems fair to conclude from these studies that, in general, the frequency of coronary heart disease is greater among the groups with higher socio-economic standards, though there may be epidemiologically important exceptions to this rule which demand further study [70]. This conclusion has little meaning in itself unless the factors related to these gradients can be identified.…”
Section: International Comparisonsmentioning
confidence: 99%